Studi Akumulasi Logam Timbal (Pb) dan Efeknya Terhadap Kandungan Klorofil Daun Mangrove Rhizophora mucronata - Aulia Dewi Puspita; Adi Santoso; Bambang Yulianto (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro, 2014)
Mangrove is a coastal plant which is vurneable to heavy metal pollution , whether from land or from the sea . More industrial development resulted in high levels of waste pollution .Various industrial waste into coastal waters will threat coastal vegetation like as mangrove. Rhizophora mucronata is one kind of mangrove with the highest population and is most often found around the coastal areas. Many industrial activities dischange lead (Pb), where Pb is one of the heavy metals that can not be degraded, can be accumulated in organism. This study aimed to know the accumulation of plumbum in mangrove the influence of difference concentration of Pb and exposure duration on chlorophyll content of R. mucronata mangrove leaves. The research was conducted in July-August 2012 at the Marine Science Campus , Faculty of Fisheries and Marine Science , Diponegoro University , Semarang. Mangrove saplings used was R. mucronata ± 8 months old . Mangrove test was placed on the test media with concentrations of 20 , 100 , and 500 ppm . Each treatment was triplicates and analysis for chlorophyll content was done every 10 days. The results of study can be concluded that the greater Pb concentration the longer the exposure time could decrease of chlorophyll content. But despite the amount of chlorophyll decreased, based on the calculation of the value of phytoremediation (FTD) R. mucronata still be potencial to reduce pollutant movement of Pb in soil/sediment/